Performance of the first prototype of the CALICE scintillator strip electromagnetic calorimeter - Francis, Kiran; Briggl, Konrad; Eckert, Patrick; Harion, Tobias; Schultz-Coulon, Hans-Christian; Shen, Wei; Stamen, Rainer; Bilki, B.; Norbeck, E.; Northacker, D.; Onel, Y.; Wilson, G. W.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2014)
A first prototype of a scintillator strip-based electromagnetic calorimeter was built, consisting of 26 layers of tungsten absorber plates interleaved with planes of 45×10×3mm3 plastic scintillator strips. Data were collected using a positron test beam at DESY with momenta between 1 and 6GeV/c. The prototype׳s performance is presented in terms of the linearity and resolution of the energy measurement. These results represent an important milestone in the development of highly granular calorimeters using scintillator strip technology. A number of possible design improvements were identified, which should be implemented in a future detector of this type. This technology is being developed for a future linear collider experiment, aiming at the precise measurement of jet energies using particle flow techniques.
Gesehen am 09.04.2021